The Impact of Digital Transformation on Governance Principles at the Royal Oman Police from the Perspective of External Stakeholders - Al-Sharji, Azza Said Hilal; Al-Fathi, Khalifa Mohammed Said (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to explore the impact of digital transformation on the governance principles at the Royal Oman Police from the perspective of external stakeholders. The study addressed the problem of how to highlight the role of the Royal Oman Police in elevating Oman’s position in global indicators through digital transformation. The importance of the study lies in identifying the main challenges facing digital transformation that affect governance principles and assisting decision-makers and top management in developing strategic action plans to address these challenges and improve the quality of services provided to beneficiaries. A qualitative descriptive methodology was employed to achieve the study’s objective. The study population consisted of all external stakeholders benefiting from the electronic services of the Royal Oman Police, with a purposive sample of five forms of external stakeholders, namely (a government sector employee, a private sector employee, an entrepreneur, a Sanad Office employee, and a resident investor). To achieve the study’s objectives, the researchers developed a semi-structured interview tool. The interview duration ranged between 45-60 minutes. The analysis was based on extracting key themes and building general classifications according to these themes. The study results showed that digital transformation is characterized by visibility, interaction, and financial exchange, but the level of integration with other government agencies needs improvement. The results also indicated that digital transformation is characterized by transparency, fairness, integrity, and reducing the misuse of power to a good extent, but human intervention still affects the delivery of services.